Safety analysis as integral part of chemical processes intensification and integration - Zuzana Labovská; Branislav Šulgan; Juraj Labovský; Ludovít Jelemenský (Chemical Engineering Transactions, 2022)
In recent years, process intensification and integration have played a key role in the world’s production of esters. This is successfully achieved by the reactive distillation process. In this work, intensification of the ethyl acetate production process is studied comparing three case studies: conventional process set-up (ethyl acetate is produced in a chemical reactor) is designed as a base case study; reactive distillation with a separation unit is derived from the conventional process set-up, and intensified of the latter pathway by the integration of a heat pump. Effect of the intensification was evaluated by multilevel assessment based on energy requirements, economic, environmental, and safety analyses. Safety evaluation was based on the Chemical Process Quantitative Risk Analysis performing individual risk estimation for all case studies.